1999
DOI: 10.2172/4717
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Stationary Fuel Cell Technology

Abstract: l"'~T he contents. of this report are printed on recycled paper. m DISCLAIMER Portions of this document may be illegible in electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…[21] Previous studies have shown that astrocytes mediate both positive and negative responses in neuronal cells. Primary neurons co-cultured randomly with astrocytes showed reduced toxicity to ammonia [22] but an increased sensitivity to the toxicity of glutamate [23] as compared to pure neuronal cultures. Thus the ability to create and maintain neuronal and astrocyte co-cultures are crucial in developing neuronal systems to study neuron function and interactions between neurons and glial cells.…”
Section: Introductionmentioning
confidence: 95%
“…[21] Previous studies have shown that astrocytes mediate both positive and negative responses in neuronal cells. Primary neurons co-cultured randomly with astrocytes showed reduced toxicity to ammonia [22] but an increased sensitivity to the toxicity of glutamate [23] as compared to pure neuronal cultures. Thus the ability to create and maintain neuronal and astrocyte co-cultures are crucial in developing neuronal systems to study neuron function and interactions between neurons and glial cells.…”
Section: Introductionmentioning
confidence: 95%
“…The resolved flow, which includes large turbulent eddies, is solved using a filter operation to the Navier-Stokes equations (Brown 1999). Small-scale turbulence is represented by first-order turbulence closure in the subgrid model.…”
Section: The Large-eddy Modelmentioning
confidence: 99%
“…Molten carbonate fuel cell (MCFC) and solid oxide fuel cell (SOFC) are high-temperature fuel cells. MCFC and SOFC are most appropriate for stationary power production (from a few hundred kilowatt up to a few megawatt), due to their high electrical (and cogeneration) efficiencies 16 [83,84]. The efficiency of SOFC and MCFC can be further increased by integration with gas turbines (MCFC or SOFC-GT hybrids).…”
Section: Fuel Cellsmentioning
confidence: 99%